Deservingness heuristics drive redistributive choices, but weights on recipient effort vary - Pei-Hsun Hsieh; Reuben Kline (Humanities & Social Sciences Communications)
Abstract Building on the deservingness heuristic—evaluating recipients based on need and effort—from evolutionary psychology, we develop a simple model of altruism conditional on deservingness to explain individuals’ redistributive preferences. We test the model’s predictions using an incentivized experiment where participants could directly transfer their earned money to a recipient with varying levels of income and effort. When recipients’ effort is clearly signaled, most participants’ choices align with the model’s predicted need and effort effect. Using finite mixture regressions, we identify three types of redistributive preferences: highly responsive to effort, less responsive, and self-interested. These categories reflect varying weightings of recipients’ efforts within the model. Moreover, we find that redistributive patterns are associated with political ideology and economic values commonly assessed in surveys. However, when recipients’ effort is absent or ambiguous, income becomes the primary determinant of resource allocation, even when effort may be partially inferred.